(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Famous author Shashi Deshpande is well known for her works, which mostly highlight thestruggles women face and their search for personal identity. The goal of the current essay is to examinehow Shashi Deshpande’s novel A Matter of Time depicts the position of women across time. The focus ofthe book under examination is the development of the man-woman connection across four generations asthey attempt to face the truth by delving into the past. The lives of four women, Manorama, Kalyani, Sumi, Aru, who are victims of prejudice brought about by patriarchal society are depicted in this book. Withouta successful marriage, the measure of a woman’s success is her married life, and without that, all of herother accomplishments are deemed useless.